An Evaluation of Rubber-Dam Acceptability by Dental Practitioners in RAKCODS - Kalhoro, Feroze; Memon, Sikander Munir; Askari, Jodat; Dhia, Hussain; Mofti, Hareb (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
To evaluate the prevalence of usage and reasons why rubber-dam used and not being used as well as the patients concerns and to determine if rubber-dam does improve the quality of care or no. It was an Observational study. This study was conducted at RAKCODS clinics, UAE. A paper-based questionnaire was distributed to 120 candidate of 4th, 5th year clinical students and inters in RAKCODS clinics. The data collected were statistically analyzed. A low 26% of the responders answered that they always use rubber when compared to other studies done by National Dental Practice-Based Research Network which had 44% of practitioners always use rubber-dam. Patients who refuse the application of rubber-dam claimed that it is harder for them to breath, painful, lack of communication with the dentist and that they are terrified. A 90% of participants answered that the rubber-dam improved the success rate of the treatments. The study showed that rubber-dam usage in RAKCODS clinic is less than it should be. Hence promotion of rubber-dam usage must be done more effectively in pre-clinical. Solutions should be provided to eliminate the discomfort while using rubber-dam.